UMP Womens Association donates school attire - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 22 March 2023 - Concerned with the school preparation of the local community, the Universiti Malaysia Pahang Women’s Association (Matahari) organised the Back To School (BTS) 2023 Programme at the Auditorium Hall, UMP Pekan Library.